Learning Resources in Mathematics - NCERT (JOURNAL OF INDIAN EDUCATION, 2012)
To disseminate the NCERT’s initiatives of developing textbooks for two-year B.Ed. courses offered at Regional Institutes of Education, NCERT, this text on ‘Learning Resources in Mathematics’ taken from recently published textbook Pedagogy of Mathematics for two-year B.Ed. course by the NCERT is presented here for our readers. Readers may see the details of this book on the back page of this journal.